Amantadine aerosol in humans. - Knight, V (1979)
Seven well volunteers and three patients with a naturally occurring influenza A/USSR/77 (H1N1)-like infection were given amantadine by small-particle aerosol with a Collison generator modified for this purpose. Inhalation periods for the volunteers were increased on consecutive weekends from 15 min to 1 h, 4 h, 9 h, and 2 consecutive days of 6 h each. The particle size was 1.2-micrometer mass median diameter, and the concentration of inhaled aerosol ranged from 47 to 75 microgram/liter. Estimates of retained doses in 9 h were 74 to 149 mg. About two-thirds of the dose was recovered in the urine. Pulmonary function studies did not vary significantly from base-line values and were within a normal range for five of seven volunteers. Two volunteers with a moderate reduction in mid-maximal flow before exposure had a total of three episodes of coughing and wheezing associated with moderate reductions in mid-maximal flow values. These episodes cleared spontaneously or improved promptly after isoproterenol therapy. The patients with influenza tolerated the treatment well and recovered promptly.